Coaching and emotional competencies (Journal of Parents and Teachers, 2013)
This paper outlines briefly the methodology of coaching. The author of this article holds that Coaching is a methodology that has been proven to have a measurable impact on helping students to take responsibility for their actions with the guidance of their teachers. In this period in which people that dedicate their lives to education, teachers and also parents, are more worried day by day about the lack of effort of children and young people, a new tool is presented to help them in this difficult journey of acquiring emotional competences. This piece of writing also reflects how emotional competences are learned, which emotional competences and emotions encourage the learning processes focusing on provide information for the teachers to offer to their students. In addition, if the reader wants to improve in some particular area, This article teaches how to do it by coaching one’s self.
Keywords: Learning; Responsibility; Verbal communication; Non-verbal communication; Message; tutorial